Maintained Visual-, Auditory-, and Multisensory-Guided Associative Learning Functions in Children With Obsessive–Compulsive Disorder - Pertich, Ákos; Eördegh, Gabriella; Németh, Laura; Hegedüs, Orsolya; Öri, Dorottya; Puszta, András; Nagy, Péter; Kéri, Szabolcs; Nagy, Attila (Frontiers in Psychiatry, 2020)
Sensory-guided acquired equivalence learning, a specific kind of nonverbal associative learning, is associated with the frontal cortex-basal ganglia loops and hippocampi, which seem to be involved in the pathogenesis of obsessive-compulsive disorder (OCD). In this study, we asked whether visually, auditory, and multisensory guided associative acquired equivalence learning is affected in children with OCD. The first part of the applied learning paradigm investigated association building between two different sensory stimuli (where feedback was given about the correctness of the choices), a task that critically depends upon the basal ganglia. During the test phases, which primarily depended upon the hippocampi, the earlier learned and hitherto not shown but predictable associations were asked about without feedback. This study involved 31 children diagnosed with OCD according to the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-V) criteria and 31 matched healthy control participants. The children suffering from OCD had the same performance as the control children in all phases of the applied visual, auditory, and multisensory guided associative learning paradigms. Thus, both the acquisition and test phases were not negatively affected by OCD. The reaction times did not differ between the two groups, and the applied medication had no effect on the performances of the OCD patients. Our results support the findings that the structural changes of basal ganglia and hippocampi detected in adult OCD patients are not as pronounced in children, which could be the explanation of the maintained associative equivalence learning functions in children suffering from OCD.